A Combined LC-MS Metabolomics- and 16S rRNA Sequencing Platform to Assess Interactions between Herbal Medicinal Products and Human Gut Bacteria in Vitro: a Pilot Study on Willow Bark Extract - Pferschy-Wenzig, Eva-Maria; Koskinen, Kaisa; Moissl-Eichinger, Christine; Bauer, Rudolf (Frontiers in Pharmacology, 2017)
Herbal preparations are complex mixtures of natural products, many of which are able to reach the distal gut due to low oral bioavailability. There, they can influence the microbial communities, and can be metabolized into potentially absorbable bioactive compounds by the intestinal bacteria. This aspect has often been disregarded when searching for the active principles of medicinal plants and herbal medicinal products. The aim of this study was to establish an interdisciplinary platform to unravel interactions of herbal medicine and intestinal microbiota, using a combined LC-MS metabolomics and 16S rRNA microbiome sequencing approach. Willow bark extract (WBE), a herbal medicinal product with a long history of traditional use and a well-established anti-inflammatory activity, was incubated with human fecal suspension under anoxic conditions. Samples were taken after 0.5, 4 and 24 h of incubation. Microbiome analyses revealed that incubation with WBE had a marked effect on microbial community composition and functions. For example, the proportion of Bacteroides sp. was clearly enhanced in when the fecal sample used in this study was incubated with WBE-treated samples. LC-MS analysis showed that WBE constituents were readily metabolized by fecal bacteria. Numerous microbial metabolites could be annotated, allowing the construction of putative microbial degradation pathways for the main groups of WBE constituents. We suggest that studies of this type help to increase the knowledge on bioactive principles of medicinal plants, since gut microbial metabolites might have been underestimated as a source of bioactive compounds in the past.